Interdiscursivity in the series of casta paintings attributed to the New Spanish painter José Joaquín Magón (2014)
This article seeks to analyze a series of casta paintings attributed to José Joaquín Magón. Furthermore, the characteristic of including a literary legend that makesvalue judgments about the moral and social conditions of the “products” will enable the establishment of peculiarities. This study traces the relationships betweenthe casta paintings and the basic features of this pictorial genre, comparing them with a series that Magón was ordered to paint and which was taken to Spain by the archbishop Lorenza. Finally, we examine the problematic condition of the relationship between legend, box, and work in this series, and eventually, based on theanalysis of interdiscursivity, we consider taxonomy and the socio-racial classiication represented in this series of miscegenation paintings.